2022
DOI: 10.3390/foods11172613
|View full text |Cite
|
Sign up to set email alerts
|

Natural Antimicrobials: A Clean Label Strategy to Improve the Shelf Life and Safety of Reformulated Meat Products

Abstract: Meat is a nutrient-rich matrix for human consumption. However, it is also a suitable environment for the proliferation of both spoilage and pathogenic microorganisms. The growing demand to develop healthy and nutritious meat products with low fat, low salt and reduced additives and achieving sanitary qualities has led to the replacement of the use of synthetic preservatives with natural-origin compounds. However, the reformulation process that reduces the content of several important ingredients (salt, curing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 148 publications
(276 reference statements)
0
13
0
Order By: Relevance
“…The quantification of the bioactive compounds by the HPLC method show that the quality of propolis added to the cooked ham formulation was good according to its phenolic profile. The content in flavonols (quercetin, galangin, and kaempferol), phenolic acids (p-coumaric acids and esters of caffeic and ferulic acids), and flavones and flavanones (chrysin and pinobanksin), are by previous works describing propolis from the exact geographical origin [5,24,[40][41][42]. These compounds have demonstrated their bioactivity through a broad antimicrobial activity spectrum.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…The quantification of the bioactive compounds by the HPLC method show that the quality of propolis added to the cooked ham formulation was good according to its phenolic profile. The content in flavonols (quercetin, galangin, and kaempferol), phenolic acids (p-coumaric acids and esters of caffeic and ferulic acids), and flavones and flavanones (chrysin and pinobanksin), are by previous works describing propolis from the exact geographical origin [5,24,[40][41][42]. These compounds have demonstrated their bioactivity through a broad antimicrobial activity spectrum.…”
Section: Discussionmentioning
confidence: 95%
“…These compounds have demonstrated their bioactivity through a broad antimicrobial activity spectrum. For instance, the antibacterial activity of quercetin, p-coumaric acid, caffeic acid, and their derivatives occurred against bacterial species such as S. aureus, L. monocytogenes, and B. cereus [2,5]. Most flavonoids and phenolic acids identified in the selected propolis exhibited biological activity against Gram-positive and Gram-negative food-borne pathogens, as displayed by the low minimum inhibition concentrations [35].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, scientists around the world are trying to innovate and create better solutions to battle the current challenges associated with the multidrug resistance of pathogenic microorganisms and their impact on the healthcare system and infectious diseases. In light of this, nature-based materials are generally considered safe and renewable and have demonstrated additional properties, such as antioxidant behavior, a broad antimicrobial spectrum, activity against sensitive and resistance pathogens, and some have been shown to reverse antibiotic resistance . Therefore, they could be a good candidate to address the abovementioned challenge and provide alternative or complementary technologies to conventional antibiotics. Several reports have demonstrated that polyphenols, such as lignin, , possess a broad spectrum of antimicrobial activities (Figure ).…”
Section: Combined Catalysis: An Innovative and Sustainable Tool For E...mentioning
confidence: 99%